Complete casting handbook : metal casting processes, metallurgy, techniques and design - Campbell, John, 1938- (Elsevier Butterworth-Heinemann, 2011)
Complete Casting Handbook is the result of a long-awaited update, consolidation and expansion of expert John Campbell's market-leading casting books into one essential resource for metallurgists and foundry professionals who design, specify or manufacture metal castings. The first single-volume guide to cover modern principles and processes in such breadth and depth whilst retaining a clear, practical focus, it includes: A logical, two-part structure, breaking the contents down into casting metallurgy and casting manufacture Established, must-have information, such as Campbell's '10 Rules' for successful casting manufacture New chapters on filling system design, melting, molding, and controlled solidification techniques, plus extended coverage of a new approach to casting metallurgy Providing in-depth casting knowledge and process know-how, from the noteworthy career of an industry-leading authority, Complete Casting Handbook delivers the expert advice needed to help you make successful and profitable castings. Long-awaited update, consolidation and expansion of expert John Campbell's market-leading casting books into one essential handbook. Separated into two parts, casting metallurgy and casting manufacture, with extended coverage of casting alloys and new chapters on filling system design, melting, moulding and controlled solidification techniques to compliment the renowned Campbell '10 Rules'. Delivers the expert advice that engineers need to make successful and profitable casting decisions.